Beyond the Calculus of Power and Position: Relationships and Theorizing in Ethnography. (November 2019) - Tavory, Iddo
Ethnography is made of relationships. Even when the observations the ethnographer writes of take place between others in the field, it is through the development of relationships that data are generated and through a particular relationship that interpretation is offered. In this introduction to the special issue about relationships and theorizing in ethnography, I outline three relevant dimensions of such relationships that aren't captured by current debates that center on power dynamics in the field: (a) Alignment. Going beyond the trifecta of race, class, and gender, I suggest that a key element of positionality includes the ways in which the ethnographer's projects align (or purposely fail to align) with those of her interlocutors; (b) Temporality. Thinking seriously about time allows us to appreciate how differences in the temporal arcs of research modulate the narrative arcs of theory as well as set the stage for the afterlife of participant observation in the process of writing and publishing; and (c) Place. As relationships deepen, ethnographers often find themselves in new spaces, complementing the temporality of narrative arcs with a different landscape of social theory. Doing so, this article calls for renewed attention to the way in which the patterned structure of relationships in the field shapes how ethnographers theorize their work.